2017
DOI: 10.4064/fm140-4-2016
|View full text |Cite
|
Sign up to set email alerts
|

Strong homology, derived limits, and set theory

Abstract: We consider the question of the additivity of strong homology. This entails isolating the set-theoretic content of the higher derived limits of an inverse system indexed by the functions from N to N. We show that this system governs, at a certain level, the additivity of strong homology over sums of arbitrary cardinality. We show in addition that, under the Proper Forcing Axiom, strong homology is not additive, not even on closed subspaces of R 4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…To begin with, it fully disentangles the combinatorial and algebraic components of arguments whose hybridity had hitherto been an impediment to their comprehension. It thereby facilitates a much closer analysis of the set-theoretic content of these arguments, and this, indeed, is our work's main contribution: we show that the partition hypotheses PH n hold for all universally Baire partitions of powers of ω ω; this carries the corollary that for all n ∈ ω all universally Baire n-coherent families of functions indexed by ω ω are trivial, answering Questions 6 and 7.12 of [2] and [4], respectively, and generalizing a main result of [31]. Moreover, the associated trivializations can themselves be taken to have low complexity relative to the n-coherent family; in particular, in the presence of suitable large cardinal hypotheses, they are universally Baire.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…To begin with, it fully disentangles the combinatorial and algebraic components of arguments whose hybridity had hitherto been an impediment to their comprehension. It thereby facilitates a much closer analysis of the set-theoretic content of these arguments, and this, indeed, is our work's main contribution: we show that the partition hypotheses PH n hold for all universally Baire partitions of powers of ω ω; this carries the corollary that for all n ∈ ω all universally Baire n-coherent families of functions indexed by ω ω are trivial, answering Questions 6 and 7.12 of [2] and [4], respectively, and generalizing a main result of [31]. Moreover, the associated trivializations can themselves be taken to have low complexity relative to the n-coherent family; in particular, in the presence of suitable large cardinal hypotheses, they are universally Baire.…”
Section: Introductionmentioning
confidence: 59%
“…In Section 3 we introduce refinements of the standard topological and Baire measurability structures on powers of ω ω and in Section 4 we show that the hypotheses PH n hold for partitions which are measurable with respect to these structures. We obtain as an immediate corollary a negative answer to the question, appearing in both [2] and [4], of whether a nontrivial n-coherent family may be analytic.…”
Section: Introductionmentioning
confidence: 90%
“…Standard resolutions convert this description to a more concrete general form, as before. The characterisations of lim 1 A and of lim A ( ≥ 1) in [22] and [4], respectively, then each involve one further conversion, via the long exact sequence…”
Section: Homological Backgroundmentioning
confidence: 99%
“…Moore further observed therein that 'it is entirely possible that it is a theorem of ZFC that either lim 1 A ≠ 0 or lim 2 A ≠ 0 .' The first set-theoretic computation of lim 2 A appeared some seven years later in [4]; here framings of lim A ( > 1) in terms of higher-dimensional coherence were given and applied to show that the Proper Forcing Axiom implies that lim 2 A ≠ 0. Here also Goblot's work [13] was applied to show that ≤ ℵ implies that lim A = 0 for all > .…”
Section: Introductionmentioning
confidence: 99%
“…The study of the triviality of coherent families of functions indexed by ω ω dates to [1]; there, Mardešić and Prasolov showed that the additivity of strong homology implies that every coherent family is trivial. Higher-dimensional variants of these notions were introduced in [10]; these encoded the behaviors of the higher derived limits associated to the system A described above. In this section, we further generalize these notions to s-coherence and s-triviality for arbitrary Ω-systems G, and we analyze their relationship to these systems' associated higher derived limits.…”
Section: Higher Coherence and The Derived Limit Lim Smentioning
confidence: 99%